Floating photovoltaic technology definition aided with multi-criteria decision analysis: a case study - Salvatore Di Grazia; Giuseppe Marco Tina (International Journal of Sustainable Energy, 2022)
The demand for electrical energy is constantly growing. Power generation from renewable sources will play a role in meeting the electricity demand. Floating photovoltaics is a solution that still needs to be explored in the design and construction phases. The floating system has important characteristics: it reduces evaporation of water and algae growth in the basins, it does not occupy land and has a high efficiency due to the evaporative cooling effect. Multi-criteria decision analysis is used to determine the best technology, between fixed or tracked structure, on a system in Sicily. Analysis provided results regarding the superiority of horizontal axis tracking systems; the Levelized Cost Of Electricity is 64.37 USD/MWh and the avoided CO2 emissions are 23,491.60 tonnes.